FAKTOR – FAKTOR YANG MEMPENGARUHI ENVIROMENTAL DISCLOSURE : TINJAUAN LITERATUR - Riska Amelia Kamil; Dona Primasari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Environmental issues have become a topic in today's global economy. InIndonesia, complaints about cases of environmental damage received by theMinistry of Environment and Forestry have increased from year to year, so thereis a need for accountability for environmental sustainability which can be statedin the form of disclosures regarding company operational activities that have animpact on the environment. This study aims to analyze the related factors thatcan influence a company to make environmental disclosures. This research is aliterature review on Environmental Disclosure which is based on 20 empiricalstudies from national and international journals. The research data wasobtained through internet searches regarding Environmental Disclosure articlespublished in 2014 – 2021. The results of this study are that there are 31dependent variables studied in 2014 – 2021, for the most studied variables arefirm size, leverage and environmental performance variables. Dependentvariables that have a positive and significant effect on environmental disclosure:Board size, proportion of non-executive directors, foreign ownership, mediacoverage, earnings management, independent audit, auditor type, listing age.Dependent variables that have no effect on environmental disclosure:Proportion of Muslim directors, female directors, gender diversity, governmentownership structure, institutional ownership structure, block holder ownership,public ownership structure, company age, corporate governance perceptionindex, stock exchange listing, audit committee, Industry Type. Dependentvariables that do not have a negative effect on environmental disclosure: boardgender, liquidity, . Dependent variables that still have different results in severalarticles: Board of commissioners size, company size, audit committee size,proportion of independent commissioners, leverage, profitability, managerialownership , Educational background of the commissioner president, Boardmeetings, Environmental Performance.